2011
DOI: 10.1063/1.3609073
|View full text |Cite
|
Sign up to set email alerts
|

Fe solubility, growth mechanism, and luminescence of Fe doped ZnO nanowires and nanorods grown by evaporation-deposition

Abstract: Fe doped ZnO nanowires, nanorods, and urchin-like nanostructures have been grown using an evaporation-deposition method with compacted mixtures of ZnS and Fe 2 O 3 powders, with different Fe contents as precursors. Treatments at 950 C under argon flow lead to the growth of iron doped nanowires, nanorods, and other nanostructures on the surface of the compacted sample. The incorporation of iron into the nanostructures has been investigated via energy dispersive spectroscopy as well as by cathodoluminescence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“… and some differences in the CL spectra due to Te doping of ZnO were observed. This behaviour has been observed in many other systems .…”
Section: Resultssupporting
confidence: 78%
“… and some differences in the CL spectra due to Te doping of ZnO were observed. This behaviour has been observed in many other systems .…”
Section: Resultssupporting
confidence: 78%
“…Previously, in many works [61] it was specified that when using gas-phase methods for producing NPs, irrespective of Fe mass content in targets, the mass content of Fe dopant in the final product does not exceed 1 mass% that will be coordinated in relation to ours by results.…”
Section: Structural and Element Analysis Of Nanopowdersmentioning
confidence: 99%
“…In works [61][62][63][64] it is shown that Fe ions in nanomaterials (thin films, various nanostructures, nanopowders, etc.) on the basis of ZnO-Fe can be in two-or three-valent condition separately, and in the mixed valent condition, depending on the method and conditions of producing materials.…”
Section: Structural and Element Analysis Of Nanopowdersmentioning
confidence: 99%
“…2(c), slightly red shifts to 1.69 eV and the FWHM narrows to 0.57 eV, which can be interpreted by a configurational coordinate (CC) model [24]. Furthermore the absence of any fine structure in the peak at 15 K eliminates the assignment of the observed RL to transition metal impurities, such as Fe, Co and Ni, which exhibit characteristic sharp features due to internal 3d transitions [25,26]. The presence of a broad emission at 2.5 eV has been attributed to surface and bulk V O centers at 5 K [19,27].…”
Section: Resultsmentioning
confidence: 97%